2022
DOI: 10.3390/molecules27144388
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Methane Hydrate Formation with Butterfly Turbine Impellers

Abstract: Heat generation during gas hydrate formation is an important problem because it reduces the amount of water and gas that become gas hydrates. In this research work, we present a new design of an impeller to be used for hydrate formation and to overcome this concern by following the hydrodynamic literature. CH4 hydrate formation experiments were performed in a 5.7 L continuously stirred tank reactor using a butterfly turbine (BT) impeller with no baffle (NB), full baffle (FB), half baffle (HB), and surface baff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In other papers [ 64 , 65 ], the kinetics of the copolymerization of DADMAC with a vinyl ether of ethylene glycol at 70 °C in the presence of initiator (K 2 S 2 O 8 ) was studied. It was found that by increasing the initiator concentration from 1.3 × 10 −2 to 1.75 × 10 −2 mol × L −1 , the rate of the copolymerization reaction increased from 1.13 × 10 −4 to 1.28 × 10 −4 mol × L −1 × s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…In other papers [ 64 , 65 ], the kinetics of the copolymerization of DADMAC with a vinyl ether of ethylene glycol at 70 °C in the presence of initiator (K 2 S 2 O 8 ) was studied. It was found that by increasing the initiator concentration from 1.3 × 10 −2 to 1.75 × 10 −2 mol × L −1 , the rate of the copolymerization reaction increased from 1.13 × 10 −4 to 1.28 × 10 −4 mol × L −1 × s −1 .…”
Section: Resultsmentioning
confidence: 99%